PENGARUH PERTUMBUHAN EKONOMI DAN INDEKS PEMBANGUNAN TERHADAP KEMISKINAN DI KABUPATEN MERAUKE - Romualdus Turu Putra (Musamus Journal of Economics Development, 2024)
The study aims to determine the impact of economic growth and the Human Development Index on Poverty in Merauke District 2015-2022, the type of data used is secondary data from 2015 to 2020. The research approach used was a quantitative approach, a method based on the philosophy of positivism and using double linear regression analysis with the help of SPSS version 26. Data analysis using quantitative associative methods and the analysis techinique used is multiple linear regression analysis with the help of the SPSS version 26 application. The results of the study show that partially the economic growth variable has a positive and significant effect on poverty in Merauke Distric with a coefficient value of 0,062 and a signivicance value of 0,029. While the human development index variable has a nagative and insignificant effect on poverty in Merauke District with a coefficient value of -0,060 and a significance value of 0,072. Simultaneously variable human development index and economic growth have an influence on poverty in Merauke District. Keywords: Economic growth, Human Development Index and Poverty